Conversion of ALD CuO Thin Films into Transparent Conductive p‐Type CuI Thin Films - Alexander Weiß; Jacqueline Goldmann; Sakari Kettunen; Georgi Popov; Tomi Iivonen; Miika Mattinen; Pasi Jalkanen; Timo Hatanpää; Markku Leskelä; Mikko Ritala; Marianna Kemell (Advanced Materials Interfaces, 2023)
Abstract Copper iodide (CuI) is a high‐performance p‐type transparent semiconductor that can be used in numerous applications, such as transistors, diodes, and solar cells. However, the lack of conformal and scalable methods to deposit CuI thin films limits its establishment in applications that involve complex‐shaped and/or large substrate areas. In this work, atomic layer deposition (ALD) is employed to enable scalable and conformal thin film deposition. A two‐step approach relying on ALD of CuO and its subsequent conversion to CuI via exposure to HI vapor at room temperature is demonstrated. The resulting CuI films are phase‐pure, uniform, and of high purity. Furthermore, CuI films on several substrates such as Si, amorphous Al2O3, n‐type TiO2, and γ‐CsPbI3 perovskite are prepared. With the resulting n‐TiO2/p‐CuI structure, the easy and straightforward fabrication of a diode structure as a proof‐of‐concept device is demonstrated. Moreover, the successful deposition of CuI on γ‐CsPbI3 proves the compatibility of the process for using CuI as the hole transport layer in perovskite solar cell applications in the nip‐configuration. It is believed that the ALD‐based approach described in this work will offer a viable alternative for depositing transparent conductive p‐type CuI thin films in applications that involve complex high aspect ratio structures and large substrate areas.